Communication in Oncology Outpatient Clinic Settings: Congruence of Quality of Life Assessment between Patient-Physician and Patient-Caregiver Dyads. (25th August 2022) - Tang, Chia-Chun; Hsi, Chen; Wei-Wen, Wu; Tsai, I-Ni; Jaw-Shiun, Tsai
Abstract : Context . Exploring the congruence of health-related quality of life (HRQOL) evaluation provides valuable information regarding whether proxies can accurately reflect patient perceptions and the quality of symptom communication. It is particularly important in advanced cancer population who experience poor HRQOL and have deteriorated ability to express their feelings. Objectives . The aims of this study were to investigate the congruence of HRQOL reports between patient-physician and patient-caregiver dyads and to determine the association of variables, if any, with the congruence between dyads. Methods . This correlational study with a cross-sectional design first approached physicians who provided care for patients with advanced cancer at the participating institution. Then, participating physicians' patients and their caregivers were recruited. All participants were required to independently fill out an HRQOL questionnaire during their outpatient visits. Descriptive statistics, weighted kappa, Wilcoxon signed-rank test, and linear regression were employed for data analysis. Results . A total of 52 patient-physician and 27 patient-caregiver dyads were examined. Patients suffered from considerable problems in all three HRQOL domains: symptom, functioning, and overall HRQOL. The patients' level of agreement was moderate with the caregivers and fair with the physicians. A significant relationship was found between several patient-related variables and disagreement. Conclusion . These patients with advanced cancer experienced a compromised HRQOL, warranting immediate attention. When there are barriers to obtaining a patient's self-report, clinicians may consider caregivers as a reasonable source. Patients with special characteristics need additional attention because their problems may be at a greater risk of being overlooked.